2022
DOI: 10.3133/sir20225067
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of per- and polyfluoroalkyl substances and inorganic analytes in groundwater and surface water used as sources for public water supply in West Virginia

Abstract: Concentrations of chemical constituents in water are given in either milligram per liter (mg/L), microgram per liter (µg/L), or nanogram per liter (ng/L). viii Abbreviations 9Cl-PF3ONS 9-chlorohexadecafluoro-3-oxanonane-1-sulfonate 11Cl-PF3OUdS 11-chloroeicosafluoro-3-oxaundecane-1-sulfonate 4:2 FTS 4:2 fluorotelomersulfonate 6:2 FTS 6:2 fluorotelomersulfonate 8:2 FTS 8:2 fluorotelomersulfonate ADONA 4,8-dioxa-3H-perfluorononanoate CEC contaminants of emerging concern DO dissolved oxygen DoD U.S. Department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
0
9
1
Order By: Relevance
“…We find that concentrations of targeted and nontargeted PFAS are higher in surface water than in groundwater and observed the highest PFAS concentrations in a remote tributary with a lower industrial footprint than locales along the Ohio River. These findings are contrary to initial observations made in the state-wide study of PFAS in West Virginia, 41 which found PFAS concentrations were generally higher in groundwater than surface water sources and at sites along the western boundary of the state near the Ohio River, emphasizing the importance of high-resolution sampling efforts from a variety of sources and locales.…”
Section: Evaluation Of Variable Significance Using a Multivariate Lat...contrasting
confidence: 99%
See 2 more Smart Citations
“…We find that concentrations of targeted and nontargeted PFAS are higher in surface water than in groundwater and observed the highest PFAS concentrations in a remote tributary with a lower industrial footprint than locales along the Ohio River. These findings are contrary to initial observations made in the state-wide study of PFAS in West Virginia, 41 which found PFAS concentrations were generally higher in groundwater than surface water sources and at sites along the western boundary of the state near the Ohio River, emphasizing the importance of high-resolution sampling efforts from a variety of sources and locales.…”
Section: Evaluation Of Variable Significance Using a Multivariate Lat...contrasting
confidence: 99%
“…49 These wells, like most private wells, are infrequently tested, 45,50 but they may be at a particular risk from PFAS contamination owing to this region's legacy of PFAS-generating industrial activities coupled with the recent acceleration in UOG development. 51 According to a recent study, 24% of 279 public water systems tested in the northern Appalachian state of West Virginia exhibited concentrations in source waters of at least one PFAS compound above the study's minimum reporting level (10 ng/ L) 41 ; however, the sources of PFAS could not be determined, and PFAS concentration in private well waters were not measured. Consequently, questions remain regarding PFAS levels in private water wells and whether these concentrations are reflective of those observed in public water systems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported the highest detection frequencies of PFAS in surface waters of the Ohio River from the districts 5 and 6. 23 River otters inhabiting districts 5 and 6 are thus likely exposed to elevated PFAS concentrations. We divided the samples into two categories based on potential waterborne exposure from fluoropolymer facilities: districts 1−4 (N = 36) and districts 5−6 (N = 6).…”
Section: Tissue Distributionmentioning
confidence: 99%
“…22 Industrial releases of PFOA from a fluorochemical manufacturing facility at Parkersburg, West Virginia (WV) (Figure 1), into the Ohio River and the surrounding environment received considerable attention. 23 Elevated concentrations of PFOA were reported in surface water and drinking water in areas affected by historical releases from the fluorochemical facility. 23 Serum concentration of PFOA in an exposed human community in WV (geometric mean: 32.9 ng/ mL) was 8-fold higher than that of the U.S. general population in 2003−2004 (3.9 ng/mL).…”
Section: Introductionmentioning
confidence: 99%